Proteomic analysis of salicylic acid regulation of grain filling of two near-isogenic rice (Oryza sativa L.) varieties under soil drying condition - Kimbembe, Romesh Eric Romy (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 The Authors. Published by Elsevier Masson SAS.. All rights reserved.